The study on cause and effect of abandoned housing project in selangor - Nur Farhayu, Ariffin; Mohd Faizal, Md Jaafar; Mohamad Idris, Ali; Noram Irwan, Ramli; Khairunisa, Muthusamy; Saffuan, Wan Ahmad; N. H., Abd Khalid (IOP Publishing Ltd, 2018)
Construction industry is one of the most dynamic, risky, and challenging industries not only in Malaysia but other countries too. The main issues facing by the construction industry is abandoned building project. The issue of abandoned building had happened across the globe and brings negative impact to the nation and country. In Malaysia, the magnitude of this issue has grown to an unbearable state. According to the Sales and Purchase agreement, abandoned building is a construction work in a project site that has been continuously stalled for 6 months or more, whether during the project completion period or beyond the scheduled date of completion. When the projects of the building become abandoned, it gives an adverse effect such as downfall of economic growth. Besides, it will cause a serious problem of sustainability especially a waste of natural resources/material used for the construction. In order to prevent this problem, some mitigation plan is needed. This study was conducted to study the cause, effect and economic analysis on abandoned project. There is a need for broader discussions on its implications to the society and nation. The questionnaire survey was conducted and distributed to most civil engineers around Malaysia. The results was analysed using average index methods and likert scale. The result shows that there are many factors that contribute to the abandoned building project which mostly comes from the developer management itself. The loss of money when the project is abandoned is unneglectable. A mitigation plan need to be done in order to revive the abandoned project therefore, it will help in growth of economy in Malaysia.